Pengaruh Latihan Lompat Box terhadap Daya Ledak Otot Tungkai pada Ekstrakurikuler Bola Voli Putra SMP Siempat Teran Naman - Rio Sandri Deni Surbakti; Janwar Frihasan Sinuraya; Deasyi Natalia Sitepu (PT. Penerbit Tiga Mutiara, 2026)
This study was motivated by the importance of lower-limb explosive power in volleyball, particularly in supporting smashing, blocking, and jumping serves, while evidence regarding the effectiveness of box jump training among male extracurricular participants at SMP Siempat Teran Naman remains limited. The study aimed to analyze the effect of box jump training on the lower-limb explosive power of male volleyball extracurricular participants at SMP Siempat Teran Naman using an experimental method with a one-group pretest-posttest design. The subjects were 15 participants aged 13–15 years selected through total sampling, who underwent box jump training for four weeks at a frequency of three sessions per week, with lower-limb explosive power measured using the Vertical Jump Test before and after training. The results showed that the average explosive power increased from 41.40 cm to 49.80 cm, while the paired-sample t-test produced a t-value of 14.21 > t-table of 2.145 with a significance value of 0.000 < 0.05, indicating a significant difference. These findings demonstrate that structured and progressive box jump training can serve as a practical alternative for improving lower-limb explosive power while supporting volleyball development in schools.